Genetic analysis of the enterobactin gene cluster in Shigella flexneri. - Schmitt, M P (1991)
The genes for transport and synthesis of the phenolate siderophore enterobactin are present on the chromosomes of both Ent+ and Ent- clinical isolates of Shigella flexneri. To determine why Ent- S. flexneri isolates fail to express a functional enterobactin system, the structure and expression of enterobactin genes were examined. Several alterations may be responsible for the inability of S. flexneri to express enterobactin. (i) The mRNA levels produced from the entC and fepB genes were not derepressed in low-iron media. (ii) DNA sequence analysis of the entC-fepB intergenic region revealed an 83-bp noncontiguous deletion in the putative fepB leader sequence. The deleted sequences are in a region which would be capable of forming extensive stem-and-loop structures. (iii) An amber codon in the 5' portion of the entC gene was also detected. (iv) An IS1 element, previously mapped to the Ent- S. flexneri enterobactin gene cluster, was found to lie within a potential transcriptional termination sequence in the entF-fepE intergenic region. (v) A mutation responsible for the inactivation of the entF gene was mapped to the entF coding region by using entF hybrid gene fusions. (vi) A comparison of outer membrane profiles from an E. coli strain harboring the cloned fepA gene from either an Ent+ or Ent- Shigella isolate revealed that the Ent- FepA protein is present in the outer membrane but at greatly reduced levels than that of the Ent+ FepA protein. This observation, along with additional studies, suggests that the Ent- FepA may be defective in translation and/or translocation.